2016
DOI: 10.1080/19420862.2015.1130196
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of ch14.18/CHO in relapsed/refractory high-risk neuroblastoma patients treated by long-term infusion in combination with IL-2

Abstract: (2016) Pharmacokinetics and pharmacodynamics of ch14.18/CHO in relapsed/refractory high-risk neuroblastoma patients treated by long-term infusion in combination with IL-2, mAbs, 8:3, 604-616, DOI: 10.1080/19420862.2015 To link to this article: https://doi.org/10. 1080/19420862.2015 .8 mg£d/ml, respectively, were not significantly different. Importantly, we detected ch14.18/CHO trough concentration of 1 mg/ml at time points preceding subsequent antibody infusions after cycle 1, allowing a persistent activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 17 publications
6
54
0
5
Order By: Relevance
“…Ab concentrations were determined as previously described. 6 We found no difference in ch14.18/CHO levels between patient cohorts (data not shown, p D 0.782 and p D 0.642 for FCGR2A high vs. low and FCGR3A high vs. low cohorts, respectively). These data show that differences in ADCC levels observed are not related to varying ch14.18/CHO concentrations.…”
Section: 7-fold Respectively)mentioning
confidence: 87%
See 2 more Smart Citations
“…Ab concentrations were determined as previously described. 6 We found no difference in ch14.18/CHO levels between patient cohorts (data not shown, p D 0.782 and p D 0.642 for FCGR2A high vs. low and FCGR3A high vs. low cohorts, respectively). These data show that differences in ADCC levels observed are not related to varying ch14.18/CHO concentrations.…”
Section: 7-fold Respectively)mentioning
confidence: 87%
“…5 We further showed that this novel delivery method of ch14.18/ CHO induced Ab effector mechanisms (ADCC and CDC) over the entire treatment period of 6 mo and may therefore emerge as the preferred delivery method of anti-GD 2 Ab in NB patients. 6 We reported ch14.18/CHO C max concentrations of 12.56 § 0.68 mg/mL and a CDC activity of 88 § 2%, showing a low degree of variability in contrast to patient-specific ADCC levels of 21 § 3% at this time point. 6 This variation in ADCC may be associated with many factors including the cytotoxic activity of effector cells such as natural killer (NK) cells, monocytes, neutrophils and macrophages that play a crucial role in Ab-mediated antitumor effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human anti-mouse antibody (HAMA) responses against murine mAbs can reduce the efficacy of the antibody immunotherapy by neutralizing the antibody, not allowing for effective recruitment of immune cells to the tumor site. It is possible that the frequent induction of a neutralizing (HAMA) response to 3F8 vs. the infrequent induction of a human anti-chimeric antibody (HACA) response to ch14.18 (23,24), or the use of IL2, may somehow account for the differential association of KIR-ligand missing status with better outcome for anti-GD2 treated patients in the MSKCC regimen but not the COG regimen.…”
Section: Discussionmentioning
confidence: 99%
“…2. Ганглиозид GD2 является целью для GD2-направленной иммунотерапии [55][56][57][58]. Он в большей степени экспрессируется на клетках первич-ной НБ.…”
Section: индивидуализация терапии с помощью молекуляр-ных таргетных пunclassified